Corallocarpus glomeruliflorus: Pharmacological potential revealed by phytochemical and in silico investigations - Fatima Saleh Naji Bin-Asal; Adel A.M. Saeed; Abdul-Rahman Alawi Bin Yahia (Biochemistry and Biophysics Reports)
Corallocarpus glomeruliflorus (CGP), a plant native to Yemen, has been traditionally used for the management of various health conditions, including cancer, inflammation, and diabetes. This study presents the first comprehensive phytochemical and pharmacological investigation of CGP, revealing novel molecular mechanisms and therapeutic potential. Phytochemical analysis of the CGP extract revealed the presence of diverse bioactive compounds, including phenols, flavonoids, and other secondary metabolites. Notably, this is the first report identifying maritimetin, assafoetidin, kaempferol 3-rhamnoside 7-xyloside, and lespenefril in CGP, compounds with significant therapeutic potential. The total phenolic content was 88.12 ± 4.48 mg GAE/g, significantly higher than previously reported for related species (63.78 ± 1.27 mg GAE/g), and the total flavonoid content was 22.1 ± 0.01 mg QE/g. The extract demonstrated superior antimicrobial activity against Pseudomonas aeruginosa compared to previous studies, with a zone of inhibition of 16.7 ± 1.53 mm at 200 mg/mL concentration. The CGP extract displayed strong antioxidant activity in DPPH, FRAP, and phosphomolybdenum assays, with an IC50 value of 48.39 ± 1.58 μg/mL in the DPPH assay, compared to 9.88 ± 0.54 μg/mL for the positive control ascorbic acid. Most significantly, the CGP extract exhibited more potent selective anticancer effects on human breast (MCF-7) and colon (HCT-116) cancer cell lines than previously reported for related Cucurbitaceae species, with IC50 values of 49.18 ± 2.81 μg/mL and 244.2 ± 9.86 μg/mL, respectively. Our novel molecular docking studies revealed previously unreported interactions between CGP compounds and key therapeutic targets, particularly Pim-1, PIK3CA, α-amylase, and Gyr-B, providing new insights into its mechanism of action.